Experience in commissioning the halcyon linac. Issue 10 (27th August 2019) - Netherton, Tucker; Li, Yuting; Gao, Song; Klopp, Ann; Balter, Peter; Court, Laurence E; Scheuermann, Ryan; Kennedy, Chris; Dong, Lei; Metz, James; Mihailidis, Dimitris; Ling, Clifton; et al.
Abstract : Purpose: This manuscript describes the experience of two institutions in commissioning the new Halcyon TM platform. Its purpose is to: (a) validate the pre‐defined beam data, (b) compare relevant commissioning data acquired independently by two separate institutions, and (c) report on any significant differences in commissioning between the Halcyon linear accelerator and other medical linear accelerators. Methods: Extensive beam measurements, testing of mechanical and imaging systems, including the multi‐leaf collimator (MLC), were performed at the two institutions independently. The results were compared with published recommendations as well. When changes in standard practice were necessitated by the design of the new system, the efficacy of such changes was evaluated as compared to published approaches (guidelines or vendor documentation). Results: Given the proper choice of detectors, good agreement was found between the respective experimental data and the treatment planning system calculations, and between independent measurements by the two institutions. MLC testing, MV imaging, and mechanical system showed unique characteristics that are different from the traditional C‐arm linacs. Although the same methodologies and physics equipment can generally be used for commissioning the Halcyon, some adaptation of previous practices and development of new methods were also necessary. Conclusions: We have shown that the vendor pre‐loaded data agree well with the independent measured ones during the commission process. This verifies that a data validation instead of a full‐data commissioning process may be a more efficient approach for the Halcyon. Measurement results could be used as a reference for future Halcyon users.